Comparison of spirometric indices Veterans injured spinal cord injury athletes in various sports groups - M. Saberi; A. Ebrahimi etri; A.A. Hashemi javaheri; M. Khodaei (Afarand Scholarly Publishing Institute, 2013)
Introduction: cardiovascular fitness as the ability of the system - respiratory and skeletal muscle to achieve a certain level of activity is defined as, where after spinal cord injury can be reduced through exercise can increase this capacity. Objective: The objective of this study, veterans with spinal cord injury spirometric indices in various athletic sports (Archery, wheelchairrany , swimming, , wheelchair basketball) and is a non-athlete. Methods: Therefore, this study on 60 veterans in 48 veteran spinal cord injury spinal cord injury athletes(12 athletes Archery, 12 athletes wheelchairrany, 12 athletes swimming, 12 athletes , wheelchair basketball) Were veterans and 12 non-athletes. Spirometric indices (FVC, PEF, FEF75%, FEV1, FEV1/FVC) was evaluated through spirometry device. For data analysis, descriptive statistics were used to test the assumptions in the study of inferential statistical methods such as analysis of variance ANOVA, post hoc test was used Froony bin. Results: The spirometric indices (FVC, PEF, FEF75%, FEV1, FEV1/FVC) in the disciplines of Archery wheelchairrany , swimming, , wheelchair basketball and a non-athlete group, there is a significant difference ( P <0/05). Conclusion: According to survey results, exercise regularly and choose the most appropriate sport for disabled people is essential to spinal cord injury.